MASKÁT - Niebuhr, Carsten (Tidsskriftet Antropologi, 2003)
After describing the specific religious attitudes and affiliations of the inhabitants this description of the harbour and city of Maskat in Oman turns to issues of security, trade, traffic, architecture and climatic conditions.